Knowledge of Medical and Nursing Students Regarding Breast Imaging: Pengetahuan Mahasiswa Kedokteran dan Keperawatan tentang Pencitraan Payudara - Abdul-Ra'aoof, Husham Hussain; Mizher, Wedad Amer; Tiryag, Ali Malik; Ali, Jaafer Nafie Abd; Hamza, Arkan Ali; Adb-Almoniem, Hasan Ali (Indonesian Journal on Health Science and Medicine, 2025)
General Background: Breast imaging is a cornerstone in the diagnosis and management of breast diseases, offering essential support for early detection and treatment planning. Specific Background: With the rising incidence of breast cancer globally, healthcare professionals require solid knowledge of imaging modalities such as mammography, ultrasonography, CT, and MRI. Knowledge Gap: Despite the critical role of imaging, limited evidence exists regarding the knowledge level of medical and nursing students, who represent the future healthcare workforce. Aims: This study aimed to assess the knowledge of medical and nursing students regarding breast imaging at the University of Basrah. Results: A cross-sectional survey of 150 students revealed that 77.3% demonstrated good knowledge, while the remainder showed moderate understanding, with gaps particularly concerning cancer risk distribution and technical aspects of imaging modalities. Novelty: This study provides one of the few systematic assessments of student knowledge in Iraq, highlighting both strengths and deficiencies in breast imaging education. Implications: Findings emphasize the need to enhance curricula with deeper integration of theoretical and practical components in breast imaging to ensure well-prepared graduates capable of contributing effectively to breast cancer detection and management.Highlight : Most students have good knowledge of breast imaging. Breast imaging is important for early detection of breast cancer. There are still gaps in knowledge that need to be addressed in the curriculum. Keywords : Knowledge, Students, Breast Imaging, Medical, Nursing